A Genomically Informed Education System? Challenges for Behavioral Genetics. Issue 1 (March 2018) - Sabatello, Maya
The exponential growth of genetic knowledge and precision medicine research raises hopes for improved prevention, diagnosis, and treatment options for children with behavioral and psychiatric conditions. Although well-intended, this prospect also raise the possibility — and concern — that behavioral, including psychiatric genetic data would be increasingly used — or misused — outside the clinical context, such as educational settings. Indeed, there are ongoing calls to endorse a "personalized education" model that would tailor educational interventions to children's behavioral and psychiatric genetic makeup. This article explores the justifications for, and prospects and pitfalls of such endeavors. It considers the scientific challenges and highlights the ethical, legal, and social issues that will likely arise should behavioral genetic data become available (or be perceived as such) and are routinely incorporated in student education records. These include: when to disclose students' behavioral and psychiatric genetic profile; whose genomic privacy is protected and by whom; and how students' genetic data may affect education-related decisions. I argue that the introduction of behavioral genetics in schools may overshadow the need to address underlying structural and environmental factors that increase the risk for psychiatric conditions of all students, and that the unregulated use of student behavioral genetic profiles may lead to unintended consequences that are detrimental for individuals, families and communities. Relevant stakeholders — from parents and students to health professionals, educators, and policy-makers — ought to consider these issues before we forge ahead with a genomically informed education system.